Risk of neurologic deficit in medially breached pedicle screws assessed by computed tomography: a systematic review - Rahmad Mulyadi; Witantra Dhamar Hutami; Kevin Dilian Suganda; Dhiya Farah Khalisha (Asian Spine Journal)
Pedicle screws are commonly used for vertebral instrumentation, and a postoperative computed tomography (CT) scan is used to evaluate their position within the pedicle. Medial pedicle screw breaching occurs in 20%–40% of cases. This study investigated the correlation between radiographically evident medial breaching and the incidence of nerve injury, shedding light on the clinical implications. A literature search was conducted on biomedical databases regarding neurologic deficits associated with medially breached pedicle screws with pre-defined inclusion and exclusion criteria. The methodology of the included studies was analyzed, and a systematic review and meta-analysis were performed to investigate the correlation between medial breach on axial CT and clinical neurologic deficits. Our study included thirteen articles. Medial breaches <2 mm caused no neurologic deficit. Medial breaches of 2–4 mm increased the risk of neurologic deficit by 83%, with a risk ratio of 0.17. Breaches exceeding 4 mm increased the risk by 90%, with a risk ratio of 0.1, and were associated with radiculopathy or muscle weakness in 25%–100% of cases. Medial pedicle screw breaches <2 mm are safe, carrying no risk of neurologic injury. Breaches exceeding ≥2 mm significantly increase this risk. For patients experiencing new neurologic deficit (sensory or motor) after pedicle screw instrumentation, particularly in lumbar vertebrae, a postoperative axial CT scan is recommended to identify breaches exceeding 2 mm as the potential cause of neurologic deficit.